2021
DOI: 10.1002/oa.2964
|View full text |Cite
|
Sign up to set email alerts
|

Bushmeat skeletal waste from an Atlantic African rainforest (Equatorial Guinea) as a test for the Mammal Community Structure Analysis in paleoecology

Abstract: Mammalian Community Structure Analysis (MCSA) is a widely used paleoecological method for reconstructing environments in fossil sites where apes and hominins are present. However, any fossil assemblage is the result of complex ecological and taphonomic processes that may obscure biological interpretation. In this work, we test the validity of the MCSA for the reconstruction of African rain forest environments through an actualistic approach. For this purpose, we compare the living Mammalian Community Structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Tutin & Oslisly (1995) suggested that the interconnections among chimpanzees, gorillas, and humans in the Paleotropics over a period of 58,000 years BCE likely modulated their current behavior after sharing the same landscape and resources in Gabon and central Africa. Rosas et al (2021) compared in the same tropical region the mammalian community structure of the mainland rainforest of Equatorial Guinea with animal skeletal remains found in villages of the region. The authors suggest that, in general, both faunal assemblages match, having frugivorous mammals as preferred prey and most diagnostic biotic signals.…”
Section: Archaeoprimatology Meets the Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…Tutin & Oslisly (1995) suggested that the interconnections among chimpanzees, gorillas, and humans in the Paleotropics over a period of 58,000 years BCE likely modulated their current behavior after sharing the same landscape and resources in Gabon and central Africa. Rosas et al (2021) compared in the same tropical region the mammalian community structure of the mainland rainforest of Equatorial Guinea with animal skeletal remains found in villages of the region. The authors suggest that, in general, both faunal assemblages match, having frugivorous mammals as preferred prey and most diagnostic biotic signals.…”
Section: Archaeoprimatology Meets the Presentmentioning
confidence: 99%
“…Hence, primates occupied a predominant position as top-ranked arboreal mammal game. Rosas et al (2021) proposed that these kinds of studies might serve as present-day models for understanding the paleoecological dynamics between humans and prey in past African forests. Recently, using a similar rationale, Ellwanger & Lambert (2018) indicated that primatology has been slow to bridge evolutionary and ecological timescales to understand niche construction or to understand human interactions in the context of their environment, particularly with other primates in the past.…”
Section: Archaeoprimatology Meets the Presentmentioning
confidence: 99%